Mitochondria-Associated Membrane Scaffolding with Endoplasmic Reticulum: A Dynamic Pathway of Developmental Disease - Saneto, Russell P.; Perez, Francisco A. (Frontiers in Molecular Biosciences, 2022)
Communication between intracellular organelles is essential for overall cellular function. How this communication occurs and under what circumstances alterations transpire are only beginning to be elucidated. The pathways of calcium homeostasis, lipid transfer, mitochondrial dynamics and mitophagy/apoptosis have been linked to the endoplasmic reticulum and tethering sites on the outer and/or inner mitochondrial membrane called mitochondrial associated membranes (MAM). Sensitive visualization by high powered microscopy coupled with the advent of massive parallel sequencing are elaborating the structure, while patient diseases are uncovering the physiological function of these networks. Using specific patient examples from our pediatric mitochondrial center, we expand how specific genetic pathological variants in certain MAM structures induce disease.